The potential of circular economy in the oil palm plantation to industry - Arista, Nor Isnaeni Dwi; Natalia, Cristina Evi; Sinaga, Intan Lorenza; Lestari, Wahyuni; Undari, Desti; Andryan, Ricky; Putri, Anita Hazimah; Alimatul, Muftia M (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Palm oil has become a crucial commodity because it has a high gross domestic product. The issue of the environmental effect of palm oil is still debated. On the other hand, desire become an essential aspect _ Because the production of agriculture No only For the moment but continues in the future. Studying and developing Stay About Palm is very important For knowing where Stay has been implemented. This study reviews the potency of palm oil through an analyzer potency of economy circular from cultivation to palm oil industry. The technique of deep data collection was used in writing the review. The document has been analyzed through a literature review to summarize the potential economic circular on the plantation and palm oil industry. Data search is not only limited to one country; paper from many countries has been reviewed. Studies This discusses the issue of palm oil getting its negative response and positive from various countries. However, findings show palm oil are very needed by humans. In context, waste produced _ by plantation and the palm oil industry study shows all waste can managed And converted to become something valuable. The circular economy is appropriate for increasing energy renewal in palm oil and ensuring a closed system. Management of good waste _ gives a mark plus economy from waste of palm oil so that palm oil can be sustainable in a way economy and environment.